Relationship between Delinquent Behaviour and Physics Academic Performance among Students of Federal Unity Colleges in North West, Nigeria - Nuhu , Usman Masanawa; Musa, Muhammad Umar; Adamu, Aminu Idris (Kashere Journal of Education, 2026)
The study investigated the relationship between Delinquent Behaviour and Physics Academic Performance among SS II Students of Federal Unity Colleges in North West, Nigeria. Three hypotheses were drawn and tested at .05 level of significance. A correlational research design was adopted. A multi-stage sampling technique was used, in which the cluster sampling technique was applied for the selection of States in North West Nigeria. One State was randomly selected from each cluster using the fishbowl sampling technique. The population used was two thousand one hundred and sixteen (2,116) students. Nine hundred and fifty-two (952) students were randomly selected using a systematic random samplings technique from the sampled schools. Delinquent Behaviour Scale and the scores of students’ academic performance in Physics from their Third term examinations (2024) were used. Cronbach’s Alpha reliability coefficient of 0.803 for the DBS Scale was determined. The hypothesis one was tested using a PPMC while the hypotheses two and three were tested using a t-test for independent sample. The results revealed that there was signiﬁcant relationship between Delinquent Behaviour and Academic Performance. It was also revealed that, there was signiﬁcant difference in each of Delinquent Behaviour and Academic Performance between male and female Students. The study concluded that delinquent behaviour correlates with the academic performance of physics students in the area. The study recommended, among others, that Students should be enlightened about the relevance of delinquent behaviours on their Achievement.